Design and optimization of heat exchanger networks based on pinch analysis - Ebrada, Leni C. (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
In this study, pinch analysis was applied to improve the energy efficiency of a brewery. The brewery's existing thermal energy consumption to produce 518 hectoliters of beer is 10,482 kW. At ~Tmin of 10°C, the minimum heating and cooling requirements of the brewery were 5,185 kW and 3,039 kW, respectively corresponding to a maximum of 22% heat recovery potential. These results were consistent with the values generated by Aspen Energy Analyzer. Heat exchanger networks (HENs) utilizing the existing hot and cold utilities of the brewery were designed for maximum energy recovery. Above pinch, 120 possible configurations were identified but only 8 are feasible. Below pinch, only 7 designs are feasible out of 52 possible configurations for designs having 1 to 3 process-to-process heat exchangers (PHEs). The optimum HEN (1 PHE and 8 process-to-utility heat exchangers) for the brewery was obtained by combining the configurations of the least cost feasible designs for both above and below pinch. The USD 432,133/year total annualized cost for the optimum HEN is 4.5% less than the existing operating cost of the brewery.
Thesis (M.S. Energy Engineering)--University of the Philippines, Diliman
Keywords: Heat exchangers; Industries -- Energy consumption